Characterization of a psychrotrophic Arthrobacter gene and its cold-active beta-galactosidase. - Trimbur, D E (1994)
Enzymes with high specific activities at low temperatures have potential uses for chemical conversions when low temperatures are required, as in the food industry. Psychrotrophic microorganisms which grow at low temperatures may be a valuable source of cold-active enzymes that have higher activities at low temperatures than enzymes found for mesophilic microorganisms. To find cold-active beta-galactosidases, we isolated and characterized several psychrotrophic microorganisms. One isolate, B7, is an Arthrobacter strain which produces beta-galactosidase when grown in lactose minimal media. Extracts have a specific activity at 30 degrees C of 2 U/mg with o-nitrophenyl-beta-D-galactopyranoside as a substrate. Two isozymes were detected when extracts were subjected to electrophoresis in a nondenaturing polyacrylamide gel and stained for activity with 5-bromo-4-chloro-indolyl-beta-D-galactopyranoside (X-Gal). When chromosomal DNA was prepared and transformed into Escherichia coli, three different genes encoding beta-galactosidase activity were obtained. We have subcloned and sequenced one of these beta-galactosidase genes from the Arthrobacter isolate B7. On the basis of amino acid sequence alignment, the gene was found to have probable catalytic sites homologous to those from the E. coli lacZ gene. The gene encoded a protein of 1,016 amino acids with a predicted molecular mass of 111 kDa. The enzyme was purified and characterized. The beta-galactosidase from isolate B7 has kinetic properties similar to those of the E. coli lacZ beta-galactosidase but has a temperature optimum 20 degrees C lower than that of the E. coli enzyme.